2021
DOI: 10.3389/fpsyg.2021.761106
|View full text |Cite
|
Sign up to set email alerts
|

Chinese University EFL Teachers' Perceived Support, Innovation, and Teaching Satisfaction in Online Teaching Environments: The Mediation of Teaching Efficacy

Abstract: This study investigated the relationships between university EFL teachers' perceived teaching support, teacher innovation, and teaching satisfaction in online teaching environments, especially the mediating role of teaching efficacy. The results of an online questionnaire survey with 473 university EFL teachers revealed that although online peer support did not directly make any difference to teacher innovation and teaching satisfaction, greater perceived support in the form of teaching resources and teaching … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 44 publications
(98 reference statements)
0
13
0
1
Order By: Relevance
“…Subjective well-being reflects the level of well-being of people according to their subjective evaluation of their lives and work (41). For teachers, the higher level of teachers' subjective well-being, the more satisfied they are with their teaching performance; therefore, the anxiety present in their daily teaching becomes weaker (76). In addition, when teachers are in a good job environment, that is, when they are provided with sufficient job resources but have low job demands, their teaching satisfaction is enhanced and their anxiety tends to be alleviated.…”
Section: Research Model and Hypothesesmentioning
confidence: 99%
“…Subjective well-being reflects the level of well-being of people according to their subjective evaluation of their lives and work (41). For teachers, the higher level of teachers' subjective well-being, the more satisfied they are with their teaching performance; therefore, the anxiety present in their daily teaching becomes weaker (76). In addition, when teachers are in a good job environment, that is, when they are provided with sufficient job resources but have low job demands, their teaching satisfaction is enhanced and their anxiety tends to be alleviated.…”
Section: Research Model and Hypothesesmentioning
confidence: 99%
“…It is well acknowledged that self-efficacy is positively connected with online learning outcomes ( Honicke and Broadbent, 2016 ). Bandura (1997) identified four sources of self-efficacy: performance accomplishments, vicarious experience, social persuasion, and physiological and emotional states, and previous studies have shown that students’ self-efficacy in online learning may be enhanced by the support connected with the four sources ( Abbitt and Klett, 2007 ; Han et al, 2021 ).…”
Section: Literature Reviewmentioning
confidence: 98%
“…Therefore, the quality evaluation of online teaching in colleges and universities can not only supervise the professional construction of colleges and universities in the special period but can also provide references and suggestions for the development of online teaching pattern. On the basis of combing the literature related to classroom teaching [62][63][64] and teaching satisfaction [6,65,66], combined with the features of online teaching, 4 criteria levels and 14 attribute levels that affect the quality of online teaching, such as teacher factors, student factors, classroom factors and technical factors, are extracted to form an online teaching quality evaluation index system. The details are shown in the following Table 1.…”
Section: Construction Of the Online Teaching Quality Evaluation Index...mentioning
confidence: 99%